Extrarenal extracranial rhabdoid tumor of the pelvis in a young adult-management of a challenging case - Bharti Devnani; Ahitagni Biswas; Sameer Bakhshi; Seema Kaushal; Tripti Nakra (Indian Journal of Medical and Paediatric Oncology)
Rhabdoid tumor commonly occurs in the kidney and has an aggressive clinical course with high mortality. Central nervous system is the most common extrarenal site. Extrarenal extracranial rhabdoid tumor (EERT) is rare. EERT usually presents in childhood, and presentation in adulthood is extremely rare. This tumor is often difficult to diagnose, and there is no established standard of care due to the paucity of cases. We herein report a case of extrarenal rhabdoid tumor of the pelvis in a young adult and discuss the presentation and possible treatment options of this rare tumor.